Chronic Diseases and Labor Force Participation Among Presenile and Senile Chinese - Qiao, Xiaotuo; Wang, Bo; Guo, Haifeng (Frontiers in Public Health, 2021)
Background: The incidence of chronic diseases has increased sharply due to China’s rapid aging and lifestyle changes in decades. The population above 45years old is an important participant in the labor force market and the health status directly affects their labor force participation decision. This study aims to explore the relationship between chronic diseases and labor force participation of elderly Chinese over 45 years old. Method: We use the multivariate probit model (MVP) to construct five structural equations for analysis. The advantage of this model is that it can deal with the endogeneity of chronic diseases. Results: First of all, compared with the elderly, younger people are more likely to participate in the labor force market; the influence of chronic diseases is greatest for presenile females in decision-making of labor force participation; the impact of psychological problems on labor force participation can’t be ignored, especially for males aged above 45. Besides, Socio-demographic factors such as geographical location and marital status also have direct effect on the probability of labor force participation while the impact of family wealth and family number are much smaller. Finally, unhealthy lifestyles have negative and indirect marginal effects on labor force participation through chronic diseases. Conclusions: This paper proves that chronic diseases have negative impact on the labor force participation for Chinese aged above 45. The public should give more tolerance and opportunities to these groups. Population aged above 45 is more vulnerable and faces more psychological problems which will lead to a decline in the labor force participation. Mental health counseling and services are urgently needed. As the urban areas enjoy more social welfare, Chinese welfare policy needs to be tilted towards the rural elderly. For individuals, maintaining healthy lifestyles can help you stay away from chronic diseases and stay in the labor force market.